If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4v + -4 = -12 Reorder the terms: -4 + 4v = -12 Solving -4 + 4v = -12 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 4v = -12 + 4 Combine like terms: -4 + 4 = 0 0 + 4v = -12 + 4 4v = -12 + 4 Combine like terms: -12 + 4 = -8 4v = -8 Divide each side by '4'. v = -2 Simplifying v = -2
| 4x+6(-2x-3)=-23-3x | | (2x+4)(x)=198 | | 9[8-(-7x-9)]=126x+234 | | 2(6-4x)=25 | | 45x-123+56=0 | | 4x+1(2)=3x-5(3) | | x+y=-2y+4 | | 40=1(x-1/2)2+x | | 0.2(6x-5)=8 | | 5x-2x+1=8x+11 | | .2(5x-1)+2.25=2(3.5+x) | | 3x+x+78+3x=180 | | 30x^2-49= | | 2(1+2)+5=x | | 0.2x-1.8=0.2 | | 3(2n-1)+3n=6n+9-n | | 18=k+5k | | 4ln(x+8)-5=0 | | 2(4y-7)-4(y-6)= | | 9y-(2y-3)=80 | | 2(47-7)-4(y-6)= | | 15+57= | | 2(x+5)=7x-5 | | (9+u)(2u+3)=0 | | f(x)=-x^2-6x-9 | | (-5+4i)(-2+2i)=0 | | (15-7)m= | | -4+25x=20x+8 | | 6g+12=6g+12 | | 20+4v= | | 4+25x=-4+24x | | -90=10(x+4) |